Discourse of Alternative Identity in Nobel Prize Lectures of Latin American Writers - QAMAR ABBAS ALVI (دریافت)
The Term ‘Latin America’ is used to describe the region of America where Romance Languages (Derived from Latin) such as Spanish, Portuguese and French are spoken. This region is renowned for its Diverse Culture, Rich History Stunning Landscapes, Encompassing Tropical Rainforests, Andean Mountains and Caribbean Beaches. Notable writers such as Gabriela Mistral, Miguel Angel Asturias, Pablo Neruda, Gabriel Garcia Marques, Octavio Paz and Mario Vargas Llosa hail from this region and have been awarded the Nobel Prize. These Nobel Laureates often explore issues specific to their home countries or regions including social injustice, Resistance and struggle for social change, National and Personal Identity, Economic Inequality and Human Rights enriching the global discourse with their unique perspective and experience. This article is a Close Reading of These Nobel Laureates speeches.